Financial development and FDI inflows in China - Hameed Khan; Umair Khan (Kiel Institute for the World Economy (IfW), 2019)
In this paper, the authors revisit the nexus of financial development and FDI inflows in Chinese perspective, incorporating the vital role of institutional quality and other important variables in this paradigm. Using ARDL bound testing and VECM procedures, they establish causality by exploiting variations in financial development and FDI. To unmask the shortcomings in the previous literature, the authors use a composite index of financial development, recently developed by the IMF, since it provides a more fine-grained analysis. The results show that there is a long-run relationship between FDI and financial development. Bidirectional causality is confirmed by using VECM. The inclusion of control variables, e.g., institutional quality, transport infrastructure, per capita GDP, trade openness, domestic investment, natural resources rent, is robust in the analysis. The positive role of financial development in FDI inflows is of utmost importance for policymakers and the Chinese government. Several policy implications are given in this study.
Keywords: C22; F23; F38; G21; G32; O17; 330; financial development; FDI; ARDL; liberalization; capital market; money market